Kilometer-Scale Larval Dispersal Processes Predict Metapopulation Connectivity Pathways for Paramuricea biscaya in the Northern Gulf of Mexico - Liu, Guangpeng; Bracco, Annalisa; Quattrini, Andrea M.; Herrera, Santiago (Frontiers in Marine Science, 2021)
Fine-scale larval dispersal and connectivity processes are key to species survival, growth, recovery and adaptation under rapidly changing disturbances. Quantifying both are required to develop any effective management strategy. In the present work, we examine the dispersal pattern and potential connectivity of a common deep-water coral, Paramuricea biscaya, found in the northern Gulf of Mexico by evaluating predictions of physical models with estimates of genetic connectivity. While genetic approaches provide estimates of realized connectivity, they do not provide information on the dispersal process. Physical circulation models can now achieve kilometer-scale resolution sufficient to provide detailed insight into the pathways and scales of larval dispersal. A high-resolution regional ocean circulation model is integrated for 2015 and its advective pathways are compared with the outcome of the genetic connectivity estimates of corals collected at six locations over the continental slope at depths comprised between 1,000 and 3,000 m. Furthermore, the likely interannual variability is extrapolated using ocean hindcasts available for this basin. The general connectivity pattern exhibits a dispersal trend from east to west following 1,000 to 2,000-m isobaths, corresponding to the overall westward near-bottom circulation. The connectivity networks predicted by our model were mostly congruent with the estimated genetic connectivity patterns. Our results show that although dispersal distances of 100 km or less are common, depth differences between tens to a few hundred meters can effectively limit larval dispersal. A probabilistic graphic model suggests that stepping-stone dispersal mediated by intermediate sites provides a likely mechanism for long-distance connectivity between the populations separated by distances of 300 km or greater, such as those found in the DeSoto and Keathley canyons.